Pengembangan Media Permainan TESABEN (Tebak Salah Benar) Sebagai Media Promosi Kesehatan Peningkatan Kesadaran Aktivitas Fisik - Aini Zahra; Putri Rahayu Sya'baniah; Khoiriyah Isni; Ayu Saidah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Gameshow is a type of non-drama or non-fiction program where a number of contestants are recorded intensively to compete for prizes. The game show that is being held is a game related to physical activity, with the game name TESABEN, a game that sharpens the player's thinking in determining which choices are right and which are wrong from the statements given. Physical activity is all activities that cause an increase or expenditure of energy that is important for physical and mental maintenance and can maintain quality of life. In this study using research and development methods, namely Research and Development or R&D. This research aims to create products that can increase adolescents’ knowledge and awareness regarding the importance of physical activity. The research was conducted by exploring potential problems by analyzing the material and media needs of the research target group. The purpose of exploring the potential of this problem is to determine the material needed and the media that are of interest to the target group. A total of 6 teenagers with an age range of 17 - 25 years became respondents to this material and media needs analysis. Then the research was continued by developing health promotion media which was validated by media experts and material experts using a questionnaire validation assessment. TESABEN game media delivered with various information about physical activity as a whole will have a positive impact so that it can be used as an alternative medium for learning which can be the first step to increase understanding related to physical activity.